HAK NAFKAH BEKAS ISTRI PNS SETELAH PERCERAIAN DITINJAU DARI PP NO 10 TAHUN 1983 JO. PP NO.45 TAHUN 1990 DAN KOMPILASI HUKUM ISLAM: Studi kasus putusan No. 1867/Pdt.G/2019/PA.Mlg - Anisa Dyah Paramita; Muh. Jufri Ahmad (Gapenas Publisher, 2022)
Divorce is an event where a marriage breaks up, after a divorce, several cases will arise, one of which is the provision of a living after the divorce. Divorce between people who are not civil servants and civil servants is different because divorce and marriage of civil servants are regulated in PP no. 10 of 1983 in conjunction with PP No. 45 of 1990 where the provision of a living after a divorce is also regulated in it, the provision of a living to the ex-wife of civil servants is different from people who are not civil servants because people who are not civil servants are regulated in the KHI. This study aims to determine the provision of a living after the divorce of civil servants according to PP no. 10 of 1983 in conjunction with PP no. 45 of 1990 and the case analysis of decision no. 1867/Pdt.G/2019/PA.Mlg. The method used for this research is a normative research method. The legal materials used are primary and secondary legal materials, primary legal materials in the form of statutory regulations, secondary legal materials consisting of literature, books, and legal journals as well as religious court decisions. The results of this study are that if a husband who is a civil servant divorces his wife, the wife is entitled to get 1/3 of the salary from her husband, but this rule is contrary to the KHI, so giving 1/3 of the salary is very irrelevant and the rule must be revised. However, in the decision No. 1867/Pdt.G/2019/PA.Mlg the husband is obliged to give 1/3 of his salary to his ex-wife and pay court fees during the trial